2015
DOI: 10.1346/ccmn.2015.0630405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grinding and Sonication on the Crystal Structure of Talc

Abstract: Talc is an important industrial mineral with a broad range of applications. Particle size and crystal structure have a significant influence on the potential uses. The present study examined the influence of grinding and ultrasound treatment on talc from a new deposit, Gemerská Poloma, in Slovakia. The general knowledge that grinding produces progressive structural disorder leading to amorphization, whereas sonication has a negligible effect on the talc crystal structure, was confirmed by X-ray diffraction (XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“… After LCC and HCC were introduced into the DSF adhesive, these characteristic calcite peaks became weak but were still present, suggesting poor compatibility with the DSF adhesive, as indicated by the discontinuous cracks and grooves on the fracture surface of DSF‐LCC and the notable HCC aggregation on the fracture surface of DSF‐HCC in Figure , both of which were detrimental to the adhesion performance. The filler TC had obvious IR absorption at approximately 3676, 1431, and 1009 cm −1 , which was assigned to the stretching modes of OH, CO 3 2− , and SiO, respectively, and the absorption at 670 cm −1 was attributed to OH bending . These characteristic IR peaks of TC still appeared with high intensity in the IR spectra of DSF‐TC, demonstrating that TC was least compatible with the DSF adhesive matrix among the five selected fillers.…”
Section: Resultsmentioning
confidence: 98%
“… After LCC and HCC were introduced into the DSF adhesive, these characteristic calcite peaks became weak but were still present, suggesting poor compatibility with the DSF adhesive, as indicated by the discontinuous cracks and grooves on the fracture surface of DSF‐LCC and the notable HCC aggregation on the fracture surface of DSF‐HCC in Figure , both of which were detrimental to the adhesion performance. The filler TC had obvious IR absorption at approximately 3676, 1431, and 1009 cm −1 , which was assigned to the stretching modes of OH, CO 3 2− , and SiO, respectively, and the absorption at 670 cm −1 was attributed to OH bending . These characteristic IR peaks of TC still appeared with high intensity in the IR spectra of DSF‐TC, demonstrating that TC was least compatible with the DSF adhesive matrix among the five selected fillers.…”
Section: Resultsmentioning
confidence: 98%
“…The shape of the peaks between 15° and 40° could be attributed to structure distortion usually caused by conditions of growth and/or metamorphization of the mineral. In addition, the distortion can be due to effects of grinding that could cause progressive structural disorder and subsequent amorphization of crystallites [ 41 ]. It is also common that during intensive grinding, the XRD basal 001 peak of talc decreases in intensity, whereas the 002 peak may disappear completely and an increase in back-ground in the 2θ = 15°–40° due to the formation of amorphous material is also expected [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the distortion can be due to effects of grinding that could cause progressive structural disorder and subsequent amorphization of crystallites [ 41 ]. It is also common that during intensive grinding, the XRD basal 001 peak of talc decreases in intensity, whereas the 002 peak may disappear completely and an increase in back-ground in the 2θ = 15°–40° due to the formation of amorphous material is also expected [ 41 ]. Another important observation made is the similarity of the XRD pattern to the one obtained by Kogure and co-workers [ 47 ] in which the authors suggested that such a pattern is typical for silicates with extensive stacking disorder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations